2020
DOI: 10.3390/ijerph17010314
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Infection Epidemiology: On the Underreporting of Norovirus Gastroenteritis Cases in Germany

Abstract: It is commonly accepted that the number of officially reported incidences of norovirus (NoV) according to the German Protection against Infection Act (Infektionsschutzgesetz) does not reflect the ‘true’ incidence of NoV in Germany. This study aims to reveal the reasons for the underreporting of NoV cases by comparing secondary data. Methods: NoV incidence (cases per 100,000 reference persons) in the age group 18–65 was derived from register data of four different sources in the German public health system (201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This is also supported by an earlier study of us. Based on register data from Lower Saxony, we showed that the incidence of NoV among HCWs was significantly higher relative to the incidence of NoV in the total population (Hofmann et al 2018).…”
Section: Discussionmentioning
confidence: 90%
“…This is also supported by an earlier study of us. Based on register data from Lower Saxony, we showed that the incidence of NoV among HCWs was significantly higher relative to the incidence of NoV in the total population (Hofmann et al 2018).…”
Section: Discussionmentioning
confidence: 90%
“…However, these studies focused on application rather than optimization and did not confirm HTS results with the gold standard Sanger methods. Due to the high degree of underreporting of norovirus cases, particularly nonnosocomial cases in healthy populations ( 17 , 18 ), samples tend to come from foodborne outbreaks requiring source attribution or chronic nosocomial cases. This skews our understanding of norovirus genotypes circulating in local populations and will limit effective vaccine production and management of clinical cases ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies focused on application rather than optimisation and did not confirm HTS results with the gold standard Sanger methods. Due to the high degree of underreporting of norovirus cases, particularly non-nosocomial cases in healthy populations (18, 19), samples tend to come from food-borne outbreaks requiring source attribution or chronic nosocomial cases. This skews our understanding of norovirus genotypes circulating in local populations and will limit effective vaccine production in the future and management of clinical cases (20).…”
Section: Introductionmentioning
confidence: 99%